A Model and Algorithm of Dynamic Map Expression and Its Application - Wan-wu Li; Lin Liu; Xu-chen Wei; Jia-jing Li; Zhaohui Liu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
On the basis of summarizing the research results of visual variables, we define six dynamic visual variables of the map symbol in this paper. We analyze the related attributes of dynamic symbols, and then construct a dynamic map expression model based on symbols. A key technology to realize dynamic expression——the key frame transform algorithm is present in the paper. The cartography process of the urban population proportion dynamic change map of the cities in Shandong province are taken as an example to demonstrate the methods and process of dynamic mapping based on the above map dynamic expression theories and models, which includes base map digitization, sorting and processing of attribute data, adding the map elements, the creation of special dynamic effect such as color transform, continuous flashing and object moving, and realization of interactive function. Finally, the paper shows the dynamic map of sea level rising influence on Qingdao, the Typhoon Soulik traveling map, the Western European natural gas trade flow variation map, the Bangkok flood risk level dynamic map, and other dynamic map effect at the end of the article.